Waste reduction through the use of single minute exchange of die in the cutting area in small and medium-sized enterprises of the textile sector - Alvarado Saenz, Alejandra Sofia (2024)
The present research identifies the issue posed by the lack of a standardized and efficient process in the cutting area of a Small and Medium-sized Enterprise in the textile-fashion sector in Peru. In an effort to address this challenge, the Single Minute Exchange of Die methodology was leveraged to enhance productivity by reducing waste associated with changeover times, manifesting as bottlenecks. Additionally, support was provided through other Lean Manufacturing tools such as 5S and SPP to propose areas for improvement that reinforce the implementation of the aforementioned technique. The results demonstrated a productivity increase of 39.36% in the area, transitioning from an average capacity of handling 3.45 orders per day to achieving a daily average capacity of up to 4.81 orders.